STRATEGIES FOR INCREASING THE SUPPLY OF INSTANT RED GINGER PRODUCTS BY THE RAJA BAWANG SME - Mohammad Reyvaldi; Muh. Fahruddin Nurdin (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2025)
SMEs are one of the important pillars in driving regional economic growth, including in the city of Palu. One product with high potential is instant red ginger produced by Raja Bawang SMEs. This study aims to formulate a strategy to increase the supply of instant red ginger products through an analysis of internal and external business factors. Primary data was obtained through observation, interviews, and sales report documentation, then analyzed using the SWOT method. The results of the study show that the greatest strength is the availability of quality raw materials and skilled labor, while the main weaknesses lie in limited production capacity, packaging design, and suboptimal promotion. Externally, the most dominant opportunity is the trend of consuming herbal products and the development of digital marketing technology, while the biggest threat comes from competition from similar products and fluctuations in raw material prices. The SWOT mapping places Raja Bawang SME in Quadrant I, which means that an aggressive strategy is the most appropriate choice. Recommended strategies include optimizing production with modern technology, product and packaging innovation, utilizing e-commerce and social media as marketing channels, and strengthening partnership networks. These findings confirm that Raja Bawang MSMEs have great potential to increase the competitiveness of instant red ginger products through the optimal utilization of internal strengths and market opportunities.